2021
DOI: 10.3390/ijms222111492
|View full text |Cite
|
Sign up to set email alerts
|

PDK1 Inhibitor BX795 Improves Cisplatin and Radio-Efficacy in Oral Squamous Cell Carcinoma by Downregulating the PDK1/CD47/Akt-Mediated Glycolysis Signaling Pathway

Abstract: Background: Oral squamous cell carcinoma (OSCC) has a high prevalence and predicted global mortality rate of 67.1%, necessitating better therapeutic strategies. Moreover, the recurrence and resistance of OSCC after chemo/radioresistance remains a major bottleneck for its effective treatment. Molecular targeting is one of the new therapeutic approaches to target cancer. Among a plethora of targetable signaling molecules, PDK1 is currently rising as a potential target for cancer therapy. Its aberrant expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 56 publications
(66 reference statements)
2
18
0
Order By: Relevance
“…Currently, the standard treatment for patients with OSCC is surgery for early-stage cancers, or surgery combined with chemotherapy, radiotherapy or targeted therapy for advanced cancer [3][4][5]. Although these constantly updated and advanced treatments have improved the quality of life of OSCC patients to a certain extent, the overall survival rate has not improved, and the 5-year survival rate of patients with advanced OSCC remains low (<50%) [6]. Radiotherapy is an important treatment strategy for patients with OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the standard treatment for patients with OSCC is surgery for early-stage cancers, or surgery combined with chemotherapy, radiotherapy or targeted therapy for advanced cancer [3][4][5]. Although these constantly updated and advanced treatments have improved the quality of life of OSCC patients to a certain extent, the overall survival rate has not improved, and the 5-year survival rate of patients with advanced OSCC remains low (<50%) [6]. Radiotherapy is an important treatment strategy for patients with OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some questions, beyond this review, also need to be answered. First, abundant studies have found OSCC with abnormal metabolism [ 191 , 192 ], however, the role of mitochondria in those processes is indistinct. Second, mitochondria can regulate the epigenetics of nuclear DNA [ 193 ], but how the nucleus regulates the epigenetics of mtDNA is indeterminate [ 194 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al reported that BX795 and BX912 might function as PDK1 inhibitors to abolish PDK1-induced c-Myc expression, resulting in cell death and a reduction in tumor sphere formation [ 239 ]. Moreover, BX795 synergizes with cisplatin to markedly reduce the epithelial-mesenchymal transition (EMT) in oral squamous cell carcinoma [ 240 ]. Dichloroacetat synergizes with the nitric oxide synthase (NOS) inhibitor T1023, reducing tumor growth [ 241 ].…”
Section: Inhibitors Targeting S6ks For Cancer Therapiesmentioning
confidence: 99%